Effects of canopy and understory nitrogen addition on the structure and eco-exergy of a subtropical forest community. (November 2019) - Tian, Yang; Lu, Hongfang; Wang, Jun; Lin, Yongbiao; Campbell, Daniel E.; Jian, Shuguang
Highlights: N-addition changed the community composition of the subtropical forest. Specific eco-exergy was more sensitive to N-addition than the usual structure indices. Understory N-addition underestimated the effects of N on the subtropical forest. The effects of N deposition on trees cannot be ignored in N loading studies. Abstract: The health of plant communities has been severely threatened by nitrogen (N) deposition across all types of ecosystems. The effect of N deposition on the structure of forest communities (as measured by the Shannon Wiener index, evenness, richness, density and biomass) has been investigated extensively, mostly through understory N-addition experiments, which has been criticized for neglecting the function of the canopy in interception, up-take and transformation of N, as well as other elements. To clarify this problem, the effects of canopy and understory N-addition on subtropical evergreen forest community structure were quantified and compared in this study. Furthermore, a bio-thermodynamic measurement, eco-exergy, was applied as a complement to the classic community structure index system to evaluate the health status of forest communities by bringing the genetic information embodied in each species into consideration. The results showed that compared to understory N-addition, richness in the shrub layer was more sensitive to the canopy N-addition. Thus, studies that only consider the effects of N-addition to the understory may underestimate the effects of N-addition on forest communities, as a whole. In this study, even though N-addition to the understory did not alter the forest structure indices (Shannon Wiener index, evenness, richness, density and biomass), significantly, it did decrease the specific eco-exergy of the subtropical, evergreen, forest community, as observed for N-addition to the canopy. The decrease was mainly contributed by the decline in the fraction of higher plants and an increase in the fraction of lower plants within the tree and herb layers. Thus, our results demonstrated that the health status of the subtropical, evergreen, forest community as determined by thermodynamic measures was more sensitive to N-addition compared to the classic community indices mentioned above, and the community structures in both tree and herb layers were also sensitive to N-addition, besides the shrub layer.